Prevalence and risk factors of small airway dysfunction and its association with smoking in China: a national cross-sectional study of 50 479 adults. Issue 1 (October 2019) - Xiao, Dan; Chen, Zhengming; Wu, Sinan; Huang, Kewu; Xu, Jianying; Yang, Lan; Xu, Yongjian; Zhang, Xiangyan; Bai, Chunxue; Kang, Jian; Ran, Peixin; Shen, Huahao; et al.
Abstract: Background: Small airways dysfunction (SAD) is common but neglected respiratory abnormality. However, little is known about its prevalence, risk factors, and prognosis in the general population of China. Methods: The nationally representative China Pulmonary Health study included more than 50 000 adults during 2012–15 using multistage stratified cluster sampling method, with valid spirometry measurements. Ten Chinese provinces, autonomous regions, and municipalities in mainland China were selected from six geographical regions, and all assessments were done in community health centres. SAD was defined as two of the three measures (ie, maximal mid-expiratory flow, forced expiratory flow 50%, and forced expiratory flow 75%) having below 65% of the predicted pre-bronchodilator values. Early-stage SAD was defined as SAD with normal forced expiratory volume in 1 sec (FEV1), forced vital capacity (FVC), peak expiratory flow, and FEV1/FVC, whereas pre-SAD was defined as early-stage SAD before bronchodilator inhalation, and pre-SAD plus post-SAD as early-stage SAD before and after bronchodilator inhalation. Logistic regression yielded adjusted odds ratios (aORs) for SAD associated with lifestyle and environmental factors. We estimated the total number of SAD in China using data from the present study and national census. Findings: Overall the prevalence of SAD, pre-SAD, and pre-SAD plus post-SAD was 43·5%, 21·4%, and 10·8%, respectively. The risk of SAD, especially pre-SAD plus post-SAD, was significantly associated with several factors, including cigarette smoking (aOR 1·16, 95% CI 1·04–1·28), exposure to particulate matter 2·5 (1·27 [1·12–1·44] at 50–74 μg/m 3, and 1·48 [1·30–1·69] at ≥75 μg/m 3 ), adiposity (1·37 [1·26–1·48] per 5 kg/m 2 higher body-mass index) and parental history of respiratory diseases (1·11, 1·02–1·21). In 2015, an estimated 426 million (95% CI 411–467), 211 million (191–242), and 104 million (94–126) adults had SAD, pre-SAD, and pre-SAD plus post-SAD, respectively, in China. Interpretation: In China, spirometry-defined SAD is highly prevalent, with cigarette smoking, air pollution, and adiposity being major modifiable risk factors. Our findings highlight the need for early screening of SAD to reduce the health burden associated with chronic lung diseases in general populations. Funding: National Natural Science Foundation of China, National Key R&D Program of China, and the Special Research Foundation for Public Welfare of Health, Ministry of Health of China.